Implications of Minimum Wage Increases on Labor Market Dynamics : Lessons for Emerging Economies - Del Carpio, Ximena V. (World Bank, Washington, DC, 2017)
This paper offers evidence on the relationship between the minimum wage and unemployment and informal employment, and identifies some of the lessons learned on the potential effects of increasing the minimum wage. Most of the evidence suggests that sizable increases in the minimum wage are likely to exacerbate unemployment and the prevalence of informal employment, which could have negative consequences for labor productivity and businesses as a result of reduced investment in employee training and loss of productive workers. This outcome occurs when businesses adopt the main channels available for absorbing increased labor costs. The majority of the empirical evidence suggests that the effects of minimum wage increases on unemployment and the demand for labor are unclear. The outcome depends in large part on the specific characteristics of the labor markets and the degree of compliance with the minimum wage law. Most of those affected by minimum wage increases are less qualified workers. In Latin American and Asia, differences in the effects of minimum wage increases depend largely on the size and type of firms. In countries with high levels of informal employment, minimum wage increases can increase informal employment, since the formal workers who lose their jobs are absorbed by the informal sector of the economy. In general, businesses have five mechanisms for absorbing the added labor costs. Given the characteristics of the labor market in emerging economies, it is likely that businesses faced with increased labor costs will resort to less than optimal channels, which will tend to affect their productivity and the labor market in general.